Aspect ratio effects on revolving wings with Rossby number consideration. (9th September 2016) - Lee, Y J; Lua, K B; Lim, T T
Abstract: Numerical simulations have been conducted to investigate the effect of aspect ratio ( AR ) on the mean lift generation of a revolving flat rectangular wing. The purpose of the study is to address some discrepancies reported in the literature regarding the influence of AR on mean lift coefficient. Here, we consider a range of AR from 1 to 10 and Rossby number ( Ro ) from 0.58 to 7.57, and our results show that different degrees of coupling between AR and Ro yield different trends of a mean lift coefficient with respect to increasing AR . The choice of reference velocity for the normalisation of mean lift forces also has a significant effect on the perceived AR effect. By isolating the effect of Ro, we found that higher AR produces higher mean lift coefficient until it plateaus at a sufficiently high AR . This finding is consistent with conventional fixed wing aerodynamics. Additionally, our results show that increasing AR reduces the three-dimensional wing tip effect and is beneficial to mean lift generation while higher Ro increases leading-edge vortex instability, which is detrimental to mean lift generation. Therefore, mean lift generation on revolving wings is dictated by the competition between these two factors, which represent two fundamentally independent phenomena.